The ACTworkbook for depression and shame : overcome thoughts of defectiveness & increase well-being using acceptance and commitment therapy - McKay, Matthew; Greenberg, Michael Jason; Fanning, Patrick (New Harbinger Publications, 2020)
"Many people with depression believe they are defective, unwanted, or inferior, and this feeling of being flawed and inadequate often leads to a strong sense of shame. Written by experienced clinicians, this workbook provides readers with practical, proven-effective skills based in acceptance and commitment therapy (ACT), so they can identify and alleviate shame-based, self-defeating beliefs, and learn to create a more fulfilling life"--